Determinants of Capital Structure: Property and Real Estate Companies (IDX) - Clarisa Sutana; Nila Pusvikasari (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The main purpose of this research is to test and analyze the impact of return on assets (ROA), firm size, tangibility, risk, and sale growth on capital structure. In this research, 8 property and real estate companies were used as samples listed on the Indonesia Stock Exchange with a total 9 years raging from the period of 2012 – 2020. The sample was selected based on purposive sampling technique. The data analysis method that were used in this research is descriptive statistics, panel data analysis model, data quality test, classic assumption tests, multiple linear regression, coefficient of correlation, coefficient of determination, goodness-of-fit test, and hypothesis test. The results of this research show that tangibility has a negative impact on capital structure. Whereas for return on assets (ROA), firm size, risk, and sale growth has no impact on capital structure.